Fashion History of the Late 19th – Early 21st Centuries as an Object of Scientific Research - Melnyk, Myroslav (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article highlights the features of fashion history as an object of scientific inquiry. Recent publications by the authors are analyzed, which reflect the specifics of contemporary research on fashion history and suggest new methodological approaches to its study. It is established that a clear concept and methodology for studying fashion history have not yet been fully developed. The article traces the emergence and practical purpose of fashion history as a scholarly field in Western countries of the 19th century. The specifics of fashion artifacts and their representations, which form the basis of fashion history visualization, are examined, along with the main restrictions of intellectual property rights that may apply to them. The article discusses the views of leading philosophers on the influence of time on the perception of the past and on the possibility of objective historical study, as well as their reflections on inductive and deductive approaches. The entrenched mythologizing of fashion history is characterized and the expediency of a critical attitude towards “style icons”, “fashion bibles” and the “fashion canon” formed on their basis is substantiated. The study argues for moving beyond these boundaries in the academic study of fashion history. It also points out possible distortions of fashion history in fashion publications and other textual or visual representations of fashion. Particular attention is drawn to the subjectivity of collection reviews and the staged nature of fashion photography, which rarely depicts real fashion. The article substantiates the need to supplement traditional sources with photographs and video recordings of “street life.” It underscores that fashion history is not identical to the history of clothing; therefore, historical research should also address fashion’s relationship with the broader socio-cultural context, its role in reflecting the “zeitgeist,” and the evolution not only of its forms but also of its semantic dimensions.